Changing tribal life: a socio-philosophical perspective - Sen, Padmaja (ed.) (New Delhi, 2003)
The essays in this book seek to understand the dynamics of change in tribal life by addressing various issues such as the Concept of Tribe, the Tribal Philosophy of Life, Concept of Value and Notion of Development. Conceptualizing the Hos of Singhbhum as a tribe, the contributors discuss at length the significance of myth and rituals among the tribals, folk treatment system, dialectics of identity and assimilation, and socio-religion of the tribes. They also examine the impact of modernity and social change on them. A sociological analysis of approaches to tribal development makes part of the volume as well.
Keywords: Tribes